Effect of circular coil dimension on resonant coupling wireless power transfer system - Mohamad, Khairul Anuar; Nain, Arif Zulfadli; Basari, Amat Amir; Haron, Ahmad Razani; Alias, Afishah; Ibrahim, Pungut (Faculty of Electronic and Computer Engineering (FKEKK), Universiti Teknikal Malaysia Melaka (UTeM), 2018)
A wireless power transfer system based on the resonant inductive coupling circuit with an additional short-range distance detection was carried out. The hardware-implemented system can be divided into four components, namely the circular coils, transmitter and receiver circuits for power transmission and microcontroller-based distance detector for the monitoring system. As the resonating capacitor is constant (1 F), different sets of inductive coils for the antenna of transmitter and receiver circuits depending on a number of turns (N) and diameter (D) were fabricated. The effect of circular loop resonant coil diameter was investigated on the output voltage and resonant frequency. The system is capable of transferring electrical energy with the maximum output voltage (VOUT) at the receiver circuits is 27.3 V. The maximum gap distance between the transmitter and receiver coils is 10 cm, corresponding to the VOUT of 4.4 V. Other than that, the maximum output power transfer (PMAX) at the receiver circuit is 15.6 W. In addition, a short-range distance detection system using an Arduino MEGA microcontroller was built to automatically monitor the output voltage with respect to the air gap distance.